Vision, Narrative, and Wisdom in the Aramaic Texts from Qumran Essays from the Copenhagen Symposium, 14-15 August, 2017 - Bundvad, Mette; Siegismund, Kasper; Sayyad Bach, Melissa; Holst, Søren; Høgenhaven, Jesper (Studies on the Texts of the Desert of Judah, 2019)
This volume is a collection of scholarly articles on the Aramaic Dead Sea scrolls, some of the oldest and most fascinating literary compositions among the ancient Jewish manuscripts found in the Qumran caves. Readership: Anyone interested in the Bible, ancient Judaism, the Dead Sea Scrolls, biblical interpretation, and the history of religion.